The Effect of Using Cross Rope Media on Learning in Elementary Schools - Anshori, Ahmad Fajar; Wiryanto, Wiryanto; Rahaju, Endah Budi (Media Pendidikan Matematika, 2025)
This study aims to examine the effect of implementing string-crossing media on the mathematics achievement of elementary school students, specifically focusing on multiplication. The research was motivated by the low performance of students in understanding multiplication concepts, which is often linked to the conventional lecture-based teaching approach and the limited use of concrete instructional tools. Employing a quantitative research method with a posttest-only control group design, the study involved 36 third-grade students from SDN Batobella 1, randomly assigned into experimental and control groups. The experimental group received lessons supported by string-crossing media, while the control group was taught using conventional methods. Data were gathered through a validated achievement test. After confirming the assumptions of normality and homogeneity, data analysis was conducted using an independent samples t-test. The results demonstrated a statistically significant difference in mean scores between the experimental group (M = 81.11) and the control group (M = 70.00), with p < 0.05. These outcomes suggest that incorporating string-crossing media substantially improves students’ learning results in mathematics. The media effectively transforms abstract multiplication concepts into concrete, visual, and interactive experiences, which particularly support students with visual and kinesthetic learning preferences. Therefore, it is recommended as a viable instructional alternative for contextual learning, especially in areas with limited access to digital educational technologies.